Socio-economic disparities between rural boroughs as a function of their peripheral location - Kluza, Krzysztof (Zróżnicowanie społeczno-gospodarcze gmin wiejskich jako funkcja ich odległości od ośrodków miejskich, 2019)
We carry out an analysis of rural areas in Poland on the LAU2 level. The research reveals significant heterogeneities among rural boroughs. The deconcentration hypothesis holds only for rural boroughs within 40 km of large towns. The remaining peripheral rural boroughs are subject to adverse demographic and development pressures, with limited infrastructure stock and public services availability. The strong differentiation between rural boroughs indicates the need for a reconsideration of the criteria for regional cohesion policies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 37-48
Keywords: regional disparities; convergence process; peripheral rural boroughs; zróżnicowanie regionalne; proces konwergencji; peryferyjne gminy wiejskie